2022
DOI: 10.3389/fmars.2022.878746
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Atlantification on a Zooplanktivorous Arctic Seabird

Abstract: Global warming, combined with an increasing influence of Atlantic Waters in the European Arctic, are causing a so-called Atlantification of the Arctic. This phenomenon is affecting the plankton biomass and communities with potential consequences for the upper trophic levels. Using long-term data (2005-2020) from a high Arctic zooplanktivorous seabird, the little auk (Alle alle), we tested the hypothesis that the Atlantification affects its diet, body condition and demography. We based our study on data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 79 publications
(108 reference statements)
1
18
1
Order By: Relevance
“…In contrast, little auk survival may be affected by changes in spring sea-ice (assuming that the detected effect is not spurious). This would be coherent with previous results found in the same population suggesting that little auk survival was affected by summer environmental conditions (Hovinen et al, 2014;Descamps et al, 2022). Indeed, Hovinen et al (2014) suggested an effect of sea surface temperatures during the breeding season of the preceding year on little auk survival, even though the time-series used was relatively short (8 years) and the results mainly driven by 1 year with high SST values.…”
Section: Implicationsupporting
confidence: 90%
See 3 more Smart Citations
“…In contrast, little auk survival may be affected by changes in spring sea-ice (assuming that the detected effect is not spurious). This would be coherent with previous results found in the same population suggesting that little auk survival was affected by summer environmental conditions (Hovinen et al, 2014;Descamps et al, 2022). Indeed, Hovinen et al (2014) suggested an effect of sea surface temperatures during the breeding season of the preceding year on little auk survival, even though the time-series used was relatively short (8 years) and the results mainly driven by 1 year with high SST values.…”
Section: Implicationsupporting
confidence: 90%
“…We did not detect any effect on Brünnich's guillemot survival or breeding success, but we found a positive effect of sea-ice with a lag of 2 years on the breeding success of little auks. In Svalbard, the little auk feeds mainly on large, energy-rich copepods (C. glacialis, stages CV; Descamps et al, 2022) whose life-history is affected by sea-ice (Ershova et al, 2021). Annual sea-ice concentration affects the abundance of early life stages of copepods (CI-CII) which are present in spring (May-June; Ershova et al, 2021).…”
Section: Potential Mechanisms Linking Sea-ice Changes and Seabird Vit...mentioning
confidence: 99%
See 2 more Smart Citations
“…The borealisation of West Svalbard fjords, due to Atlantification, is already affecting seabirds via its impacts on zooplankton (Descamps et al, 2022).…”
Section: Biomassmentioning
confidence: 99%